Developmental Dysgraphia as a Reading System and Transfer Problem: A Case Study - Fletcher-Flinn, Claire M. (Frontiers in Psychology, 2016)
This is a case study of an adolescent who had largely overcome his early difficulty in learning to read, but continued to have severe problems with spelling. He had no visual memory impairment, and his letter–sound knowledge and phonemic awareness were at adult levels. Testing revealed that his difficulties in both reading and spelling only manifested when processing unfamiliar words. He was slow and inaccurate when reading nonwords, despite a sublexical system dominated by the use of grapheme–phoneme units. It is suggested that limitations in the processing of the reading system were responsible for the lack of an extensive set of induced position-sensitive sublexical representations (ISRs) that are contextually dependent. This would have serious consequences for transfer to spelling.